Comparing Redundant and Sky-model-based Interferometric Calibration: A First Look with Phase II of the MWA - Li, W.; Pober, J.; Hazelton, B.; Barry, N.; Morales, M.; Sullivan, I.; Parsons, A.; Ali, Z.; Dillon, J.; Beardsley, A.; Bowman, J.; Briggs, F.; et al. (Institute of Physics Publishing, 2018)
© 2018. The American Astronomical Society. All rights reserved.. Interferometric arrays seeking to measure the 21 cm signal from the epoch of reionization (EOR) must contend with overwhelmingly bright emission from foreground sources. Accurate recovery of the 21 cm signal will require precise calibration of the array, and several new avenues for calibration have been pursued in recent years, including methods using redundancy in the antenna configuration. The newly upgraded Phase II of Murchison Widefield Array (MWA) is the first interferometer that has large numbers of redundant baselines while retaining good instantaneous UV coverage. This array therefore provides a unique opportunity to compare redundant calibration with sky-model-based algorithms. In this paper, we present the first results from comparing both calibration approaches with MWA Phase II observations. For redundant calibration, we use the package OMNICAL and produce sky-based calibration solutions with the analysis package Fast Holographic Deconvolution (FHD). There are three principal results: (1) We report the success of OMNICAL on observations of ORBComm satellites, showing substantial agreement between redundant visibility measurements after calibration. (2) We directly compare OMNICAL calibration solutions with those from FHD and demonstrate that these two different calibration schemes give extremely similar results. (3) We explore improved calibration by combining OMNICAL and FHD. We evaluate these combined methods using power spectrum techniques developed for EOR analysis and find evidence for marginal improvements mitigating artifacts in the power spectrum. These results are likely limited by the signal-to-noise ratio in the 6 hr of data used, but they suggest future directions for combining these two calibration schemes.